TRANSPARANSI DAN AKUNTABILITAS KEUANGAN BAGI PARA “PENDOSA - Martadinata, Sudrajat; Akbar, Arya Zulfikar (EQUITY: Jurnal Ekonomi, Manajemen, Akuntansi, 2017)
This study aims to determine the form of transparency and financial accountability at the Coin Foundation Sumbawa. Using a qualitative approach with qualitative data analysis techniques as well. Where we collect data directly plunge into the field. Interviewing informants, studying the literature, and doing triangulation of sources, data, and research time. Our successful research result concludes that the Sumbawa Coin Foundation utilizes print and online media as a means of effective, efficient, transparent and accountable information dissemination.